Decision Support System for Major Selection at SMA Muhammadiyah 1 Palembang Using the AHP Method - Iqbal, Muhamad; Ibadi, Taqrim (Jurnal Teknologi Informatika dan Komputer, 2025)
Every new school year, the school always accepts new students. Based on the rules in effect at SMA Muhammadiyah 1 Palembang, grade X students are directed to choose an existing major. SMA Muhammadiyah 1 Palembang has 2 majors, namely the science major and the social science major. Students are expected to be able to identify their interests, talents and abilities so that they do not make mistakes in choosing a major. The problem that occurs in the process of choosing a major is the difficulty in determining the student's major interests which results in a mismatch between the results of determining the major and the student's interests, talents and abilities. The choice of major in high school will affect whether they will continue to college or their future career. Many new students are still confused about choosing a major at SMA Muhammadiyah 1 Palembang. Therefore, a system is needed, and this decision-making system (DSS) is a software to solve this problem because this information system can present the best major selection for students who will register using the AHP (Analytic Hierarchy Process) method. The methodology used in developing this system is Rapid Application Development (RAD), an incremental software development process, especially for short processing times. RAD is a software process model that emphasizes short development life cycles, and rapid adaptation using component construction.